ILA'S 30 UNDER 30: Pioneers driving literacy change around the globe. - Ratner, Morgan (Literacy Today (2411-7862))
The article focuses on the International Literacy Association's 30 Under 30 honorees, celebrating their contributions to global literacy and education. Topics include empowering student leadership through initiatives like Tamara Imali Amatah's Student Voice Club, integrating technology in classrooms as seen in Shane Baker's use of digital tools, and supporting education in conflict zones, exemplified by Pashtana Durrani's work with LEARN Afghanistan.